Competitiveness of the Commodity Indonesian Coffee Beans the International Market - Adnan, Adnan; Teniro, Alwin; Zainudin, Zainudin - (Jurnal Manajemen, 2022)
The Geographical Indication Program (IG) with the application of fairtrade standardization has been launched by the Indonesian government in 2001, to increase the competitiveness of local products in the international market. This study seeks to identify the strength of competitiveness and the position of Indonesian bean coffee commodities in the international market and each of the national markets of the importing country. Panel data used during the period 2010-2021 covered 11 exporter countries and 6 importer countries, analyzed with the RCA index. The results showed that Coffee not Roasted or Decaffeinated has strong competitiveness in the international market and some national markets of importing countries, and competitiveness is weak for Coffee Roasted, not Decaffeinated. The competitiveness position of the two coffee bean commodities is in the 6th position. The occurrence of a positive correlation between the contribution of exports and the competitiveness of coffee beans indicates the positive impact of the IG program and suggests that the position of competitiveness be improved through the provision of adequate and affordable organic production facilities, farmer counseling, and partnership and promotion cooperation.